PENGARUH GAYA KEPEMIMPINAN SITUASIONAL DAN PEMBERIAN MOTIVASI TERHADAP KEPUASAN KERJA KARYAWAN PADA PT. POS CABANG DUMAI - Indah Annisa Raufa; Suryalena " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Sudarso, Buluh Kasap, Dumai Timur, Dumai City, Riau. The purpose of the study was to determine and analyze the influence of situational leadership style and motivation to influence job satisfaction partially and simultaneously. The research method used is descriptive quantitative analysis obtained from the results of questionnaires distributed to 65 respondents to employees of PT POS Dumai Branch, which is then processed with the SPSS program by conducting validity tests, reliability tests, simple linear regression analysis, multiple linear analysis, analysis of determination (R2) and test the hypothesis by testing t (partial) and F (simultaneous). The tests conducted showed that the situational leadership style had a positive and significant effect on job satisfaction, the provision of motivation had a positive and significant effect on job satisfaction, then situational leadership style and motivation had a positive and significant effect on job satisfaction for employees of PT POS Dumai Branch. Keywords: Situational Leadership Style, Motivation, Job Satisfaction